Evolutionary Phylogenetic Analysis of Isochorismate Synthase in Photosynthetic Eukaryotes - Sevan O Majed; Sardar Hussein Rasoo; Bushra K Amin; Abdulakarim Karim (Zanco Journal of Pure and Applied Sciences, 2022)
In the present research study sequence logo was used to display the frequency of conserved amino acids of multiple alignment of isochorismate synthase (ICS) sequences. The result revealed that residues in stacks with single amino acids (indicating conserved positions) were taller than those in stacks with multiple amino acids (where there is more change). The MSA result showed that different ICS sequences in different plants had a very close similarity to each other and also some amino acids in some aligned positions were highly conserved or identical. In addition, the ML tree displayed that these different ICS sequences in distinct plant species had an evolutionary relationship with each other because they shared from a single common ancestor and also have been evolved from each other through gene duplication event at the earliest stage of evolution. This event has played a key role in the evolution of different ICS enzymes in a single species called as paralogs. This event in different species has played a key role in the evolution of ICS2 from ICS1 because the variation in ICS2 happened more recently. Moreover, speciation event happened more recently and led to the evolution of different ICS enzymes in different species called as orthologs.